Biologics in inflammatory bowel disease: what are the data? - Côté-Daigneault, Justin (United European Gastroenterol J, 2015)
BACKGROUND: Over the last decade, biologics have gained an important place for the treatment of moderate to severe inflammatory bowel disease (IBD), and many randomized control trials have evaluated their efficacy. AIM: The goal of this review is to analyze the results of these trials and to highlight the evidence and indications emerging from these studies for their implementation in the management of IBD patients. METHODS: A PubMed search was realized to screen high-quality clinical trials studying biologic agents currently available in clinics for the treatment of IBD. Words used were: “infliximab,” “adalimumab,” “certolizumab,” “golimumab,” “natalizumab,” “vedolizumab,” “ustekinumab,” “azathioprine,” “methotrexate,” “Crohn's disease,” and “ulcerative colitis.” RESULTS: In Crohn's disease, studies supporting induction and maintenance therapies were documented for infliximab, adalimumab, certolizumab, natalizumab, vedolizumab, and ustekinumab. Infliximab, adalimumab, and certolizumab have evidences for fistulizing Crohn's disease and only infliximab and adalimumab have evidences for mucosal healing. In ulcerative colitis, studies supporting induction, maintenance, and mucosal healing were found with infliximab, adalimumab, golimumab, and vedolizumab. Only infliximab was associated with evidences for combination therapy with thiopurine and acute severe colitis in ulcerative colitis. CONCLUSION: Management with biologics in IBD patients is well validated by high-quality clinical trials.